The influence of packaging on consumer purchase intention of craft beer - Luís, Diogo Alexandre Afonso (2021)
The craft beer segment has been growing exponentially in Portugal, with the development of established players and the entrance of new ones. With so many different offers on the market, brands are trying to get noticed and added to shoppers’ carts, with one of the main ways of doing this being through packaging. Packaging has been a widely researched topic in marketing literature as it represents the first physical point of contact between consumers and a product, playing an essential role in attracting consumers’ attention, influencing their opinions, and impacting their decision-making process. Thus, this study aims to research the relationship between packaging/packaging elements and consumer purchase intentions of craft beer, as well as to investigate the relative importance of packaging as a purchase criterion, describe consumers’ preferences regarding craft beer packaging and identify possible trends in these preferences. To answer these questions three methodologies were employed: a semi-structured interview with the marketing manager of a Portuguese craft beer brand, two focus groups with participants of different age groups and a questionnaire of 200 respondents. Qualitative findings suggest that the importance attributed to packaging varies according to the level of consumers’ market knowledge and that, generally, packaging influences consumers’ purchase intentions. Quantitative findings suggest that label layout is the only packaging element that has an impact on consumer purchase intentions of craft beer and that there is a correlation between packaging style preference and consumers' age and gender, with younger/female consumers preferring modern packaging and older consumers preferring classic packaging.